PEMBERDAYAAN KADER "LANSIA SEROJA" = LANSIA SEHAT ROHANI JASMANI DENGAN PENGURUS CABANG AISYIAH UMBULHARJO - Bangunawati Rahajeng; Nurul Maziyyah; Zelmi Dwi Novita; Septania Dini Arviani; Satria Amurwa Wijaya (Jurnal Pengabdian Pada Masyarakat MEMBANGUN NEGERI, 2022)
Posyandu activities for the elderly, originally routine twice a month, have been stopped due to the Covid-19 pandemic. When the pandemic shifts and activities can be carried out offline again with health protocols, the cadres have difficulty reactivating activities. On the other hand, the elderly are vulnerable during the Covid-19 pandemic, so they must receive more attention. This community service is carried out to foster elderly cadres to reactivate posyandu activities for the elderly with health protocols. The UMY service team collaborated with AMC Muhammadiyah Yogyakarta Hospital in collaboration with Branch Manager Aisyiah Umbulharjo. PCA Umbulharjo cadres who became elderly cadres in their respective areas were provided with material for elderly health and healthy exercise for the elderly. The service team supervises the activities of these cadres at the posyandu for the elderly. Community service activities attended by 37 participants from 13 PRA were carried out on March 6, 2022, providing elderly health materials and elderly gymnastics. The average age of the participants was 56.45 years. Before the activity, a pretest was conducted to determine the cadres' knowledge about the health of the elderly. The average pretest value was 59.39. After debriefing and training, a post-test was held, and the average score was 85.45. From the pre-post-test value, it can be seen that there is a significant increase in the cadres' knowledge of the health of the elderly. The service team also assists elderly cadres in creating activity programs for the elderly to be physically and mentally healthy. The cadres were very enthusiastic about this community service activity. The service team hopes that the elderly cadres can do activities for the elderly and make the elderly physically and mentally healthy after the service.